The moderating effect of leader-member exchange on the relationship between safety management practices and safety performance - Teo, Wei Loong (2018)
The present study investigated the relationship between safety management practices and safety performance of nurses in Hospital Pulau Pinang. It also examined the moderating effect of leader-member exchange on the relationship between safety management practices and safety performance. The safety management practices were management commitment, safety training, safety communication and feedback, employees' involvement, safety rules and procedures, and safety promotion policies. The questionnaire consisted of 50 items adapted from previous studies. The questionnaires were distributed to 295 Grade U29 permanent nurses in Hospital Pulau Pinang for data collection, and the data were analyzed using the partial least squares-structural equation modeling (PLS-SEM). The findings showed that management commitment and safety promotion policies positively and significantly affected safety compliance, but not safety participation. Furthermore, the results also supported that employees' involvement and safety rules and procedures were positively related to safety performance (safety participation and safety compliance). Finally, managerial and theoretical implications are discussed and recommendations are made for future researchers.